Sansevieria trifasciata Prain. : A Review on Its Phytochemicals and Pharmacological Potential - Sida, Nurramadhani A; Kasmawati, Henny; Ruslin, Ruslin (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Sansevieria trifasciata Prain is known to contain phytochemical compounds and has the potential to treat various diseases. A systematic review was conducted by searching articles on Google Scholar, PubMed, NCBI, and Science Direct to gather information on identified chemical compounds and the pharmacological test results of S. trifasciata Prain leaves, both in vitro, in vivo, and in silico. The result showed that phytochemicals were derivatives of the flavonoids, alkaloids, steroids, saponins, glycosides, polyphenols, and fatty acids groups. These phytochemicals exhibit pharmacological properties, including antidiabetic, antibacterial, anticancer, antihelminthic, antimalarial, antifungal, antioxidant, antiwound healing, antianalgesic, and antiallergic properties. Acute toxicity tests indicate that S. trifasciata Prain. is safe for use, with an LC50 value exceeding 2000 mg/kgBW. We can conclude that Sansevieria trifasciataPrain. is a potential herb as medicine to treat various diseases based on its chemical compounds.Sansevieria trifasciata Prain is known to contain phytochemical compounds and has the potential to treat various diseases. A systematic review was conducted by searching articles on Google Scholar, PubMed, NCBI, and Science Direct to gather information on identified chemical compounds and the pharmacological test results of S. trifasciata Prain leaves, both in vitro, in vivo, and in silico. The result showed that phytochemicals were derivatives of the flavonoids, alkaloids, steroids, saponins, glycosides, polyphenols, and fatty acids groups. These phytochemicals exhibit pharmacological properties, including antidiabetic, antibacterial, anticancer, antihelminthic, antimalarial, antifungal, antioxidant, antiwound healing, antianalgesic, and antiallergic properties. Acute toxicity tests indicate that S. trifasciata Prain. is safe for use, with an LC50 value exceeding 2000 mg/kgBW. We can conclude that Sansevieria trifasciata Prain. is a potential herb as medicine to treat various diseases based on its chemical compounds.